Control of Diarrhoea of piglets - ΚΥΡΙΑΚΗΣ ΣΠ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The use of special supporting therapy for 7 days against diarrhoea of suckling piglets (17 days old) in combination with the proper antibiotic (apramycin sulphate) versus positive controls (medication only with the same antibiotic) gave: a) Faster control of diarrhoea and sickness. b) Better live weight gain (P<0.05) during the 14 days post treatment period. c) Better control of the stress of weaning (25 day of life). The aetiology of the possible infectious complications of the diarrhoea outbreak was based upon the presence of enteropathogenic E.coli and rotavirus.